American comics, literary theory, and religion : the superhero afterlife - Lewis, A. David (Palgrave Macmillan, 2014)
The six elements of the superhero afterlife subgenre -- The comic book medium's glimpse of eternity -- Complexities of character in Fantastic Four: Hereafter -- Planetary, Promethea, and the multiplicity of selfhood